Sports Volunteers Around the Globe Meaning and Understanding of Volunteering and its Societal Impact (Sports Economics, Management and Policy,, 2018)
This book provides an overview of perspectives and approaches to the cultural meaning of sport volunteering in different countries. The main objective is to reflect on the diversity of meanings with regard to volunteering in different cultures and societies. Additionally, this book will shed light on volunteering practices and the impact of volunteering from both an economic and a sociological perspective. The book begins with an introductory section that gives an overview of the rationale of the text and the diversity of sport volunteers in general. From there, the book's 25 chapters each discuss a specific country case study provided by researchers from the respective country. These studies provide a comprehensive overview of volunteering in each country, such as motivations of volunteers, satisfaction of volunteers, their perceived cost and benefits, and many other areas related to the overall study. By having twenty-five different countries represented and a native of each country authoring the respective chapters, this book serves as a comprehensive and diverse review of sports volunteering around the world and can be incorporated into courses in economics - particularly those dealing with sports economics - and can also be used as a reference for volunteer organizations and sports economists worldwide. .